2018
DOI: 10.1002/2017je005341
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Investigations of Habitability in Ice‐Covered Ocean Worlds

Abstract: Geophysical measurements can reveal the structures and thermal states of icy ocean worlds. The interior density, temperature, sound speed, and electrical conductivity thus characterize their habitability. We explore the variability and correlation of these parameters using 1‐D internal structure models. We invoke thermodynamic consistency using available thermodynamics of aqueous MgSO4, NaCl (as seawater), and NH3; pure water ice phases I, II, III, V, and VI; silicates; and any metallic core that may be presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
248
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 160 publications
(254 citation statements)
references
References 131 publications
(262 reference statements)
5
248
1
Order By: Relevance
“…Figure depicts the behavior with pressure of major thermodynamic properties (density, thermal expansivity, specific heat, and isothermal bulk modulus) computed using the LBF representations and seismic velocities for ices Ih, III, V, and VI. These are provided up to 2,300 MPa, on isotherms relevant to the interiors of icy ocean worlds, at 250, 260, 270, and 300 K (Lunine, ; Sohl et al, ; Vance, Planning, et al, ). Temperature has a notable effect only on specific heat and thermal expansivity which shows 20% to 30% increases with increasing temperature in this 50 K range.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure depicts the behavior with pressure of major thermodynamic properties (density, thermal expansivity, specific heat, and isothermal bulk modulus) computed using the LBF representations and seismic velocities for ices Ih, III, V, and VI. These are provided up to 2,300 MPa, on isotherms relevant to the interiors of icy ocean worlds, at 250, 260, 270, and 300 K (Lunine, ; Sohl et al, ; Vance, Planning, et al, ). Temperature has a notable effect only on specific heat and thermal expansivity which shows 20% to 30% increases with increasing temperature in this 50 K range.…”
Section: Resultsmentioning
confidence: 99%
“…Isotherms at 250, 260, 270, and 300 K are shown. The estimated pressure range found in the hydrosphere of Europa (E), Titan (T), and Ganymede (G) are reported as blue, yellow, and green bars, respectively (Vance, Planning, et al, ). Black dots on the 250 K profile represent the equilibrium pressure for the solid‐solid phase transitions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lin and Ogilvie () have shown that ohmic dissipation dominates over viscous dissipation only when Le>Eknormalm2false/3, where Ek m is the magnetic Ekman number which are, respectively, defined as Le=B0normalΩRoμρ,Ekm=νnormalmnormalΩRo2, where B 0 is the background magnetic field, μ is the magnetic permeability, and ν m is the magnetic diffusivity. Recent estimates of the electrical conductivity inside the ocean (Vance et al, ) give Ek m ∼1. The ohmic dissipation is therefore unlikely to contribute significantly to the total.…”
Section: Discussionmentioning
confidence: 99%